Determination and Prediction of the Amino Acid Digestibility of Sunflower Seed Meals in Growing Pigs - J. D. Liu (Asian-Australasian Journal of Animal Sciences, 2015)
This experiment was conducted to evaluate the chemical composition and amino acid (AA) digestibility of sunflower seed meal (SFSM) and to use this data to develop prediction equations for estimating AA digestibility for growing pigs. Ten SFSM were collected from five provinces in China. Twelve barrows (38.8±4.6 kg), fitted with ileal T-cannula were allotted into two 6×6 Latin square designs. Each of six experimental periods comprised a 5-d adaption period followed by a 2-d collection of ileal digesta. The ten test diets contained 50% SFSM as the sole source of AA. Another nitrogen-free diet was used to measure the basal endogenous losses of crude protein (CP) and AA. Chromic oxide (0.3%) was used as an inert marker in each diet. There was considerable variation (CV>10%) among the ten SFSM in chemical composition (dry matter [DM]). The concentration of CP and ether extract (EE) ranged from 29.33% to 39.09% and 0.88% to 11.33%, respectively. Crude fibre (CF), neutral detergent fibre and acid detergent fibre ranged from 21.46% to 36.42%, 38.15% to 55.40%, and 24.59% to 37.34%, respectively. There was variation among the ten SFSM in apparent ileal digestibility (AID) and standardized ileal digestibility (SID) for lysine and threonine, which ranged from 63.16 to 79.21 and 55.19% to 72.04% for AID and 67.03% to 82.07% and 61.97% to 77.01% for SID, respectively. The variation in CP and methionine ranged from 60.13% to 74.72% and 74.79% to 88.60% for AID and 66.70% to 79.31% and 77.16% to 90.27% for SID, respectively. Methionine was a good indicator to predict AA digestibility. These results indicate that conventional chemical composition of SFSM was variable (CV>10%) among the ten SFSM (DM). The results of AID, SID and prediction equations could be used to evaluate the digestibility of SFSM in growing pigs.